A Novel Hypersensitive Stripe Rust (Puccinia striiformis Westend f. sp. Tritici) Resistance Gene in Bread Wheat Cultivar Cook Effective in India - Zargar2, Ram Gopal Saini1, Mohammad Anwar Khan1*, Sajad Majeed (Journal of Phytology, 2011)
An Australian wheat cultivar Cook was studied for the stripe rust resistance both under glass house and field conditions against the most virulent races 46S119 and 78S84 of stripe rust. The inheritance studies showed that stripe rust resistance in cultivar Cook is conditioned by one hypersensitive and one non-hypersensitive genes. Apart from a known non-hypersensitive resistance gene Yr18, the cultivar cook also contains a hypersensitive stripe rust resistance gene effective against races 46S119 and 78S84. This gene could be novel and efficiently be utilized across wheat germplasm in building durable resistance against stripe rust in India.